Financial Stability in Dollarized Economies - Gulde, Anne (Occasional Papers; Occasional Paper ;, 2004)
This paper addresses the challenges to prudential supervision in highly dollarized economies, where central banks and supervisors may be constrained in the use of standard money and financial policy tools. The study's conclusions are the basis of an ongoing policy dialogue with IMF member countries, standard-setters in the financial area, and academia. The paper is part of the policy development work conducted by the IMF's Monetary and Financial Systems Department.